(untitled) (Dhaka University Journal of Science, 2012)
Maternal and child health issues continue to be at the forefront of national and global health policies. Notwithstanding the national and global policy initiatives, maternal mortality continues to be on the ascendancy in developing countries. This paper investigates the determinants of institutional delivery among a cross section of Bangladeshi women. For appropriate policy targeting, it is imperative to investigate the factors that promote institutional delivery and those that retard it. Using discrete choice model, and controlling for other covariates, we found that, women from the richest income quintile, and those that have access to health information via television delivered at appropriate health institutions. Besides, place of residence, mothers education, wanted pregnancy, utilization of antenatal care services and number of health workers visiting time inter alia were found to be significant predictors of the demand for institutional and supervised delivery. The policy implication of this finding is that health education via television is more effective than print media. Secondly, government policies meant to create jobs and increase income levels are envisaged as proper policy instrument to induce the utilization of appropriate health services including institutional delivery. Thirdly, information, education and communication (IEC) programs are urgently needed to inform women about the cause and potential risk of maternal health complications as well as the significance of institutional delivery. Finally, the use of health inputs such as antenatal care during pregnancy should be encouraged. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10337 Dhaka Univ. J. Sci. 60(1): 53-59 2012 (January)